Megamonster - Walliams, David 1971- (HarperCollins Children's Books, 2021)
On a volcanic island, in the middle of shark-infested waters, stands The Cruel School. The lessons are appalling, the school dinners are revolting and the teachers are terrifying - especially the mysterious Science teacher Doctor Doktur. When Larker is sent to the school, she quickly realises something very odd is going on... something involving Doctor Doktur, a pair of strange spectacles, and a 'Monsterfication Machine'. And ultimately she finds herself face to face with a real life Megamonster.